Environment/Data/People. [Eco] Participation through Data Visualization as Design Strategic Approach for Engaging, Sensitizing, and Educating the Community to Energy Transitionhttps://www.padjournal.net/wp-content/uploads/2024/09/04-26PAD-062024-CACCAMO-TURCO.pdf - Alessio Caccamo; Anna Turco (Pad)
In the face of a polycrisis marked by environmental, social, and economic upheavals, the transition to sustainable energy has become a global imperative. This transition is not only a matter of policy and infrastructure but also hinges on the individual citizen, who initiates and completes the process. Therefore, it is crucial for citizens to possess adequate energy literacy in line with the 2030 SDGs. Information Design plays a significant role in this scenario by creating communicative artifacts that narrate complex topics in an easily understandable manner to a broad audience. Moving from the cold, intangible dimension of data to a warm, tangible, human dimension can be achieved using visual metaphors, the creation of new levels of meaning, and the co-creation and participation in the visualization project. The physical and digital involvement with data can design a unique communicative bridge between people, the environment, and stakeholders. In this context, the participatory visualization and physicalization of data for eco-educational purposes termed [Eco] Participatory through Data Visualization - could be a promising area of investigation in communication design research and practice.